Therapeutic Efficacy of Traditional Chinese Medicine Syndrome-Based Formulae to Neuropathic Pain Caused by Chemotherapy - Liu, Yan-Wen; Chen, Ying-Jung; Chen, Yen-Hao; Tsai, Ming-Yen (Integrative cancer therapies, 2022)
Objective: Chemotherapy-induced neuropathic pain (CINP) is a troublesome complication of anti-cancer treatment. The aim of this retrospective study was to investigate the effectiveness of classic Chinese herbal formulae (CHF) Huang Qi Gui Zhi Wu Wu Tang (HQGZWWT) and Dang Gui Si Ni Tang (DGSNT) in the treatment of CINP. Materials and Methods: Douleur Neuropathique 4 (DN4) and Functional Assessment of Cancer Therapy-General (FACT-G) questionnaires were rated at baseline and after 3-monthly CHF treatment. Results: By searching through our medical records of all the CIPN patients from 2018 to 2019, we identified and enrolled 37 patients with Deficiency-Cold syndrome in the study, for whom the treatment of neuropathic pain by regular pharmacotherapies had failed or intolerable. At the third month evaluation with the DN4 questionnaire, 13 patients had symptomatic remission, 15 patients remained stable, and 9 patients had no response to CHF. The 3-month mean DN4 score was significantly higher than that at the baseline (P < .001). After CHF treatment, significant differences in quality of life were noted in the physical, social, emotional, and functional well-being subscales, and in the total score, of the FACT-G (P < .001). No adverse events or instances of disease progression were observed. Conclusions: The results of our small study are the first in the literature to show the clinical effectiveness of CHF for CINP. Combination of HQGZWWT and DGSNT is well tolerated and may offer the possibility to ameliorate CINP more than conventional care can. It merits further investigation.